2013
DOI: 10.1074/mcp.m113.029033
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals that Plasma Membrane Microdomains From Poplar Cell Suspension Cultures Are Enriched in Markers of Signal Transduction, Molecular Transport, and Callose Biosynthesis

Abstract: The plasma membrane (PM) is a highly dynamic interface that contains detergent-resistant microdomains (DRMs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 81 publications
(119 reference statements)
1
48
0
1
Order By: Relevance
“…Error bars indicate SD. represent 15% of total proteins, PMA2 showed enrichment in the DIM fraction by a factor of 3.7. These results are consistent with previous studies mostly showing a preferential association of PM-associated H + -ATPases with DIM fractions isolated from plant tissues (Mongrand et al, 2004;Borner et al, 2005;Morel et al, 2006;Raffaele et al, 2009;Srivastava et al, 2013). From these data, we concluded that PDCB1 and PDLP1 may reside in different membrane lipid environments and that the GPIanchored protein PDCB1 is likely to reside in locally confined membrane environments enriched in sterols and sphingolipids.…”
Section: The Localization Of Pdcb1 and Pdbg2 Gpi-anchored Proteins Tosupporting
confidence: 82%
“…Error bars indicate SD. represent 15% of total proteins, PMA2 showed enrichment in the DIM fraction by a factor of 3.7. These results are consistent with previous studies mostly showing a preferential association of PM-associated H + -ATPases with DIM fractions isolated from plant tissues (Mongrand et al, 2004;Borner et al, 2005;Morel et al, 2006;Raffaele et al, 2009;Srivastava et al, 2013). From these data, we concluded that PDCB1 and PDLP1 may reside in different membrane lipid environments and that the GPIanchored protein PDCB1 is likely to reside in locally confined membrane environments enriched in sterols and sphingolipids.…”
Section: The Localization Of Pdcb1 and Pdbg2 Gpi-anchored Proteins Tosupporting
confidence: 82%
“…Proteomic techniques bridge the gap between gene expression and physiological changes and provide a crucial tool to shed more light on the molecular mechanisms underlying plants’ adaptation to nutrient limitation . As an alternative of traditional 2DE, iTRAQ combined with MS/MS provides an easier access to low‐abundance proteins, as well as to membrane proteins .…”
Section: Introductionmentioning
confidence: 99%
“…The function of the remaining four GSLs has not been clarified. Similar to the CesAs, GSLs are integrated into the plasma membrane, with a putative preference for detergent-resistant membrane regions [56], and are predicted to contain 14 to 16 transmembrane domains [57].…”
Section: Callose Synthesismentioning
confidence: 99%